2009
DOI: 10.1186/1742-9994-6-23
|View full text |Cite
|
Sign up to set email alerts
|

No effect of mate novelty on sexual motivation in the freshwater snail Biomphalaria glabrata

Abstract: Background: When mating effort (e.g. via ejaculates) is high, males are expected to strategically allocate their resources depending on the expected fitness gains from a given mating opportunity. One mechanism to achieve strategic mating is the Coolidge effect, where male sexual motivation declines across repeated encounters with a familiar partner, but resuscitates when encountering a novel female. Experimental tests of male mate choice via mechanisms such as the Coolidge effect, however, remain scarce. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 59 publications
3
13
0
Order By: Relevance
“…On the other hand, mate choice has been shown to involve pre-copulatory assessment of the mating status or novelty of the partner (e.g. [42][43][44], but see [45,46]). It seems probable that this kind of preference is linked to assessing cues that can serve as a proxy for the likelihood of encountering sperm competition, and that they are therefore strongly linked to post-copulatory sexual selection.…”
Section: Pre-versus Post-copulatory Sexual Selection In Simultaneous mentioning
confidence: 99%
“…On the other hand, mate choice has been shown to involve pre-copulatory assessment of the mating status or novelty of the partner (e.g. [42][43][44], but see [45,46]). It seems probable that this kind of preference is linked to assessing cues that can serve as a proxy for the likelihood of encountering sperm competition, and that they are therefore strongly linked to post-copulatory sexual selection.…”
Section: Pre-versus Post-copulatory Sexual Selection In Simultaneous mentioning
confidence: 99%
“…Such increased motivation to mate with a novel partner, known as the Coolidge effect (Wilson et al, ), is in line with the idea that animals will allocate their ejaculates strategically if the transfer and/or production is energetically costly (Dewsbury, ; Pizzari et al, ; Koene and Ter Maat, ), thus corroborating the measurements of investment in L. stagnalis explained above. This same effect was hypothesized to occur in the sea hare, A. fasciata (Ziv et al, , but never experimentally tested), but was not found in the Ramshorn freshwater snail, B. glabrata (Häderer et al, ) and the sea slug, Chelidonura sandrana (Werminghausen et al, ).…”
Section: Measuring Gender Expression and Sex Allocationmentioning
confidence: 60%
“…1998). A recent study on the snail Biomphalaria glabrata shows that this snail does not discriminate former partners against novel partners in a second mating event that took place one hour after the first (Häderer et al. 2009).…”
Section: Discussionmentioning
confidence: 99%